Teacher preparation in Scotland - Shanks, Rachel (Emerald Publishing Limited, 2020)
This book argues that knowledge management and HRM systems should be integrated. This integration provides the foundation for designing knowledge-oriented high-performance HR practices.
Includes index.
Keywords: Teachers -- Training of -- Scotland.; Knowledge management.; Education -- Teaching Methods & Materials -- General.; Teaching skills & techniques.; elektronické knihy; electronic books